Descriptive Study of Employee Engagement With Workplace Wellness Interventions in the UK. Issue 9 (September 2021) - Mulaney, Bianca; Bromley-Dulfano, Rebecca; McShane, Erin K.; Stepanek, Martin; Singer, Sara J.
Abstract : Objective: To explore sequential steps of employee engagement in wellness interventions and the impact of wellness interventions on employee health. Methods: Using previously collected survey data from 23, 667 UK employees, we tabulated intervention availability, awareness, participation, and associated health improvement and compared engagement by participation and risk status. Results: Employees' awareness of wellness interventions at their workplaces was often low (mean 43.3%, range 11.6%–82.3%). Participation was highest in diet/nutrition initiatives (94.2%) and lowest in alcohol counseling and smoking cessation interventions (2.1%). Employees with health risks were less likely than lower-risk employees to report awareness, participation, and health improvements from wellness interventions addressing the relevant health concern. Conclusion: Employers and policymakers should consider variation in intervention engagement as they plan and implement wellness interventions. Engaging employee populations with higher health risks requires a more targeted approach. Abstract : Supplemental Digital Content is available in the text